2020
DOI: 10.1038/s41598-020-62264-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quality of life and behavioural disorders in children with persistent asthma: a Multiple Indicators Multiple Causes (MIMIC) model

Abstract: 37 , franca Rusconi 11,37 & the italian pediatric Severe Asthma network (ipSAn) program of italian paediatric Respiratory Society (ipRS) † Knowledge on multiple interdependences between quality of life (QoL) and behavioural problems in relation to asthma severity and control is undetermined. the aims of the study were: (i) to assess the relationship of QoL and behavioural problems with asthma severity and control (ii) to predict children's "abnormal/borderline" status with variation in QoL. for these purposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
2
19
0
4
Order By: Relevance
“…On the whole, the findings have been consistent that children with asthma have a higher prevalence of anxiety and depression compared with nonasthmatic control groups, 25–28 and anxiety and depression may be more prevalent the greater the asthma severity rating. A recent study by Montalbano et al 9 demonstrated that quality of life impairment and internalizing behavioral problems, especially the subscale including symptoms of anxiety and depressive symptoms, are more common in children with severe asthma than nonsevere asthma. Notably, there were no sex differences identified in that cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, the findings have been consistent that children with asthma have a higher prevalence of anxiety and depression compared with nonasthmatic control groups, 25–28 and anxiety and depression may be more prevalent the greater the asthma severity rating. A recent study by Montalbano et al 9 demonstrated that quality of life impairment and internalizing behavioral problems, especially the subscale including symptoms of anxiety and depressive symptoms, are more common in children with severe asthma than nonsevere asthma. Notably, there were no sex differences identified in that cohort.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The presence of psychiatric comorbidity in general pediatric asthma cohorts has been shown to increase symptom severity, reduce asthma control, lower quality of life, and lower medication adherence, 6 possibly mediated by heightened perception of respiratory symptoms 7 ; however, there are few data assessing anxiety and depression in children with severe asthma. 8,9 While evaluation of mental health comorbidities is highly recommended in the assessment of children with severe asthma, 10,11 there is little data specific to mental health comorbidities in the pediatric severe asthma population. Therefore, we aimed to determine the prevalence and character of mental health issues in pediatric severe asthma and its relationship to asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…It was also seen that anxiety and depression affected the control of asthma and caused frequent exacerbations of asthma in these children. In a more recent study evaluating the relationship between quality of life and behavioral disorders in children with persistent asthma, it was found that children with severe asthma were more often affected with impaired quality of life and behavioral problems 6 . Awareness of the association between anxiety and depression in children with asthma is poor especially in resource limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study evaluating the relationship between quality of life and behavioral disorders in children with persistent asthma, it was found that children with severe asthma were more often affected with impaired quality of life and behavioral problems. 6 Awareness of the association between anxiety and depression in children with asthma is poor especially in resource limited settings. This study was undertaken to identify the burden of comorbid anxiety and depression in asthmatic children belonging to our region and to find out how it affects symptom control in these children.…”
mentioning
confidence: 99%
“…Severe asthma, to a greater extent than moderate asthma, is associated with a lower quality of life and behavioural problems in children 18 . If left untreated, asthma can lead to severe respiratory distress or even death.…”
Section: Introductionmentioning
confidence: 99%